2016
DOI: 10.1152/ajplung.00298.2016
|View full text |Cite
|
Sign up to set email alerts
|

Correction of lung inflammation in a F508del CFTR murine cystic fibrosis model by the sphingosine-1-phosphate lyase inhibitor LX2931

Abstract: Progressive lung disease with early onset is the main cause of mortality and morbidity in cystic fibrosis patients. Here we report a reduction of sphingosine-1-phosphate (S1P) in the lung of unchallenged Cftr F508del CFTR mutant mice. This correlates with enhanced infiltration by inducible nitric oxide synthase (iNOS)-expressing granulocytes, B cells, and T cells. Furthermore, the ratio of macrophage-derived dendritic cells (MoDC) to conventional dendritic cells (cDC) is higher in mutant mouse lung, consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 85 publications
2
41
1
Order By: Relevance
“…Together, our findings suggest that neutrophils recruited to the airway lumen of children with CF are conditioned to adopt an activated state with distinguishing features (increased CD63 expression). This is consistent with the notion that the CF airway environment can trigger early inflammation, as previously proposed in select mouse models of CF (38,47,48), human CF fetal xenografts (15), CF ferrets (18,49), and children with CF (13). A Figure 1.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Together, our findings suggest that neutrophils recruited to the airway lumen of children with CF are conditioned to adopt an activated state with distinguishing features (increased CD63 expression). This is consistent with the notion that the CF airway environment can trigger early inflammation, as previously proposed in select mouse models of CF (38,47,48), human CF fetal xenografts (15), CF ferrets (18,49), and children with CF (13). A Figure 1.…”
Section: Discussionsupporting
confidence: 90%
“…A prime target for intervention is NE, for which inhibitors (53) should be tested for their ability to block not only extracellular, but also surface-associated forms. Alternative strategies include reducing the number of neutrophils recruited from blood (54,48) and their ability to exocytose primary granules (55).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of CF airways pathology, new interest has recently emerged for S1P as regulator of CFTR activity, as well as from the intriguing relationship between altered S1P content and inflammatory response to bacterial infection . The involvement of S1P in CF pathology is supported by evidence that inhibition of S1P degradation is associated with decreased lung inflammatory response to P. aeruginosa in a CF mouse model . In brief, abnormally elevated signaling downstream S1PRs could have detrimental effects on CF lung pathophysiology, thus making regulation of S1P/S1PR pathway a potentially relevant molecular target.…”
Section: Sphingosine and Sphingosine‐1‐phosphatementioning
confidence: 99%
“…52 The involvement of S1P in CF pathology is supported by evidence that inhibition of S1P degradation is associated with decreased lung inflammatory response to P. aeruginosa in a CF mouse model. 65 In brief, abnormally elevated signaling downstream S1PRs could have detrimental effects on CF lung pathophysiology, thus making regulation of S1P/S1PR pathway a potentially relevant molecular target. The concept of S1P as a critical regulator of host antimicrobial effector pathways has been earlier provided by Garg et al, 66 who showed that S1P reduced mycobacterial growth and pulmonary damage both in vitro and in vivo.…”
Section: Sphingosine and Sphingosine-1-phosphatementioning
confidence: 99%
“…However, treatment with SPL inhibitor (LX2931) could restore the S1P levels. Moreover, the CF phenotype of CFTR mutant mice was partially corrected by LX2931 further confirming the possible therapeutic targeting of S1P signaling in CF (50). …”
Section: Introductionmentioning
confidence: 65%